2016
DOI: 10.1590/0101-60830000000090
|View full text |Cite
|
Sign up to set email alerts
|

Heritability of social anxiety disorder: a systematic review of methodological designs

Abstract: Background: The investigation of heritability stands out as an important means to establish the weight of genetic and environmental factors in the development of social anxiety disorder. Objective: This study aims to make a critical review of methodological designs used in the investigation of the social anxiety disorder (SAD) heritability. Methods: We reviewed 31 research articles published until October 2015 and found through the electronic search bases PubMed, Web of Science, and Scopus and manual searches … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…The heritability of anxiety disorders, panic disorders and social phobia ranges from 30 to 67%, 24 30 to 60%, and 13 to 76%, respectively. 25 In other words, genetic conditions that significantly lower the fitness of individuals continue at high frequencies in human populations. Although activation of defensive mechanisms contributes to the survival of individuals according to the EMT, heightened levels of defence activation seem to be related to low fitness.…”
Section: Explanationsmentioning
confidence: 99%
“…The heritability of anxiety disorders, panic disorders and social phobia ranges from 30 to 67%, 24 30 to 60%, and 13 to 76%, respectively. 25 In other words, genetic conditions that significantly lower the fitness of individuals continue at high frequencies in human populations. Although activation of defensive mechanisms contributes to the survival of individuals according to the EMT, heightened levels of defence activation seem to be related to low fitness.…”
Section: Explanationsmentioning
confidence: 99%
“…The first insights into the genetic architecture of SAD vulnerability came from candidate gene (CG) studies and two genomewide association studies (GWASs). In the study of Trzaskowsk et al [21] on anxiety traits in 2,810 seven-year-old children, no single nucleotide polymorphism (SNP) reached the genome wide threshold for significance, and the SNPs that showed the lowest p values with relation to social anxiety traits (rs2772129 and rs2922037) could not be replicated in another similar cohort of 4,804 children. More promising were the findings of an even larger GWAS on anxiety traits by Stein et al [18], who reported two SNPs that were significantly associated with social anxiety (rs78924501 on Chr 1 in African American and rs708012 on Chr 6 in European American samples).…”
Section: Introductionmentioning
confidence: 99%
“…The hypothesis that monozygotic twins would present higher correlation of scores in instruments than the correlation of dizygotic twins was based in a variety of previous studies that presented these findings (Moreno, Osório, Martin-Santos & Crippa, 2016). In our sample, correlation values were different between monozygotic and dizygotic twins, but when confidence intervals were considered, this difference was not significative.…”
Section: Discussionmentioning
confidence: 58%
“…Although a hot topic in the field of psychopathology, estimates of heritability in SAD have presented very controversial results, mainly related to the diversity of methods used (Moreno, Martin-Santos, Osório & Crippa, 2016). Regardless, estimate the heritability of variables associated with SAD, such as facial emotion recognition, is essential to understand better the complex puzzle that leads to the development and maintenance of SAD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation